Unusual effects of Ho3+ ion on magnetic properties of YFe0.5Cr0.5O3. Issue 10 (December 2015) - Shi, L.R.; Xia, Z.C.; Wei, M.; Jin, Z.; Shang, C.; Huang, J.W.; Chen, B.R.; Ouyang, Z.W.; Huang, S.; Xiao, G.L.
Abstract: The temperature-induced dual magnetization reversal and field-induced spin reorientation transition are observed in Y0.95 Ho0.05 Fe0.5 Cr0.5 O3 . The Ho 3+ dopant improves the sensitivity of the magnetization switching and weak ferromagnetism of YFe0.5 Cr0.5 O3 . Based on the experimental results, we suggest that the ferrimagnetic ground state and the magnetization reversal mainly result from the antiferromagnetic coupling of weak ferromagnetic moments of Fe–O–Fe and Cr–O–Cr with that of Fe–O–Cr and Ho–O–Fe/Cr interactions. The fact that the magnetization reversal of Y0.95 Ho0.05 Fe0.5 Cr0.5 O3 under a lower magnetic field makes it attractive candidates for the magnetic dual sensor devices.